Creativity of nonhuman animals as narrated in the Qur'an: navigating an alternative path to sustainable development - Solihu, Abdul Kabir Hussain (2014)
Creativity is a common aspiration for individuals and organisations, and an integral part of the contemporary secular civilisation. The ability to generate novel ideas to solve practical problems in the shortest possible period has been considered a hallmark of creativity. However, in solving our collective human problems, it is common to run into conflict of interests due to our human conflicting mental orientations or cultural affiliations. Even when our human interests converge it might diverge from those of nonhuman animals. The tendency to prioritise the mental mode of operation over, or at the expense of, the workings of other nature’s inhabitants has led humans to invent things largely seen to be creative even when it is ecologically destructive. Creativity that solves an immediate, short-term problem but generates greater, long term problems is anathema to sustainable development. If creativity is seen as part of, or associated with, novelty and problem solving, creative problem solving is then a phenomenon shared by other natural beings. Nature is full of complex problems which are being solved within the network of nature’s constituents and in full compliant with nature’s design. Thus, if only for the sake of sustainability, we need to bring nature along in our conceptualisation of creativity in attempt to counteract the effects of dark side of human creativity. In promoting holistic and collective sustainability, the Qur’an makes references to some animals whose actions or modes of operation and problem solving are novel. This study identifies the creative acts of these nonhuman animals based on account given in selected Qur’anic verses.